2022
DOI: 10.3389/fimmu.2022.960412
|View full text |Cite
|
Sign up to set email alerts
|

CD19+ lineage chimerism, an early biomarker after anti-CD19 CAR-T cell therapy in patients previously receiving a hematopoietic stem cell transplantation

Abstract: Treatment targeting CD19 by a chimeric antigen receptor expressed on T cells (anti-CD19 CAR-T) has led to a breakthrough in the management and treatment of relapsed and refractory B- cell acute lymphoblastic leukemia (B-ALL). After infusion, the efficacy of anti-CD19 CAR-T is monitored by bone marrow negative minimal residual disease and the absence of peripheral CD19+ B lymphocytes (B-cell aplasia). In patients who have received an allogenic Hematopoietic Stem Cell Transplantation (HSCT) prior to treatment wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…These data suggested that BCA could be a suboptimal strategy for predicting not only CD19 negative but also CD19-positive relapses. In addition, CD19-positive lineage chimerism monitored by molecular techniques in patients who received CAR-T19 after allo-SCT, could anticipate relapse earlier than loss of BCA B-cell by MFC ( 17 ),…”
Section: Discussionmentioning
confidence: 99%
“…These data suggested that BCA could be a suboptimal strategy for predicting not only CD19 negative but also CD19-positive relapses. In addition, CD19-positive lineage chimerism monitored by molecular techniques in patients who received CAR-T19 after allo-SCT, could anticipate relapse earlier than loss of BCA B-cell by MFC ( 17 ),…”
Section: Discussionmentioning
confidence: 99%
“…Management of patients with early loss of BCA after CAR‐T cell therapy is challenging, and there is limited data to support optimal treatment. Early loss of BCA within 6 months after infusion of CAR‐T indicates loss of function, limited expansion, and persistence of the CAR‐T cells, resulting in BCA loss being used as a biomarker to recommend alloHSCT or CAR‐T reinfusion 4,49 . Some proposed mechanisms of loss of BCA are immune‐mediated rejection and development of anti‐mouse antibodies.…”
Section: Factors That May Impact the Success Of Cd19‐directed Car‐t C...mentioning
confidence: 99%
“…Loss of functional CAR‐T cells, as measured by loss of BCA, adversely affected the risk of CD19+ leukemic relapse (HR 34; 95% CI, 2.1–552; p = .01) while hazard ratio for all relapses regardless of CD19 was 3.5 (95% CI, 1.01–11.88; p = .04).Management of patients with early loss of BCA after CAR‐T cell therapy is challenging, and there is limited data to support optimal treatment. Early loss of BCA within 6 months after infusion of CAR‐T indicates loss of function, limited expansion, and persistence of the CAR‐T cells, resulting in BCA loss being used as a biomarker to recommend alloHSCT or CAR‐T reinfusion 4,49 . Some proposed mechanisms of loss of BCA are immune‐mediated rejection and development of anti‐mouse antibodies.…”
Section: Factors That May Impact the Success Of Cd19‐directed Car‐t C...mentioning
confidence: 99%